Zinc deficient diet consequences for pregnancy andoffsprings of Wistar rats - Solé, Dirceu; Rieckmann, Brigitte; Lippelt, Raquel Mattos Costa; Lippelt, Ronaldo Tadeu Tucci; Amâncio, Olga Maria Silverio; Queiroz, Suzana de Souza; Naspitz, Charles Kirov (São Paulo Medical Journal, 1995)
Adult female Wistar rats (90 days old; weight 180 to 220 grams) were submitted to different zinc deficient diets (Zn; severe = 2.6 ppm; mild = 9.0 ppm and normal diet = 81.6 ppm), during 6 weeks. After this time they were coupled with normal male Wistar rats. No differences regarding fecundity and sterility were observed between the groups. During pregnancy, part of the animals from severe and mild Zn deficient groups received the same diet and the others received normal diet. The animals from the group receiving normal diet, were divided into other 3: the first received severe, the second mild Zn deficient diet and the third normal diet. During the study we observed that animals submitted to a Zn deficient diet (acute or chronic) had tendency to lower weight gain, lower weight of the offspring, lower serum levels of Zn in maternal and newborn (pool) blood. A significant reduction in the number of alive newborns was observed in the group of animals submitted to severe Zn deficiency. These data reinforces that Zn is a very important trace element overall during pregnancy.